Membrane Inlet Mass Spectrometry: A Powerful Tool for Algal Research - Burlacot, Adrien; Burlacot, François; Li-Beisson, Yonghua; Peltier, Gilles (Frontiers in Plant Science, 2020)
Since the first great oxygenation event, photosynthetic microorganisms have continuously shaped the Earth’s atmosphere. Studying biological mechanisms involved in the interaction between microalgae and cyanobacteria with the Earth’s atmosphere requires the monitoring of gas exchange. Membrane inlet mass spectrometry (MIMS) has been developed in the early 1960s to study gas exchange mechanisms of photosynthetic cells. It has since played an important role in investigating various cellular processes that involve gaseous compounds (O2, CO2, NO or H2), and in characterizing enzymatic activities in vitro or in vivo. With the development of affordable mass spectrometers, MIMS is gaining wide popularity and is now used by an increasing number of laboratories. However, it still requires important theory and practical considerations to be used. Here, we provide a practical guide describing the current technical basis of a MIMS setup and the general principles of data processing. We further review how MIMS can be used to study various aspects of algal research and discuss how MIMS will be useful in addressing future scientific challenges.